FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA DI INDONESIA - FAUZIAH FAUZIAH; NOVIA WIJAYA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2016)
The purpose of this research is to provide empirical evidence of the affect of firm debt, firms size, firm performance, board of directors’ characteristics, managerial ownership, ownership structure, external audit quality, dividend policy and leverage ratio on earnings management. Earnings management was measure by discretionary accruals use Modified Jones Method. The population of this research are companies in the manufacturing sector which were listed in Indonesian Stock Exchange (IDX) from 2011 to 2014. The research data were collected from manufacturing companies financial statement for the period of 2011 to 2014. Based on purposive sampling method, there are 38 samples. The reseacrh hypotesis were tested using multiple regression analysis. The results of this research show that firm debt, dividen policy and leverage have significant relationships with earnings management. Meanwhile other independent variables such as firm size, firm performance, board of directors’ characteristics, managerial ownership, ownership structure, and external audit quality have no significant relationship with earnings management.